DREAMING IN CODE. - LUCAS, ROB (New Left Review)
The author examines the work conditions of a web developer in the context of classical trade union concepts of the labor-management conflict. It notes the creative tension in his company between technical and business staff and argues that each side keeps the other in check, keeping the company on track. It notes the problems inherent in any refusal of work in a 21st-century internet company, where the project is by nature a team endeavor, thus any willful slowing or sabotage of work will affect the worker negatively. It notes the development of universal standards and open source code and compares it to the state as a moral constraint on wild capitalism. It notes the decreasing boundaries between work and personal life.